Photocatalytic Oxidation of Carbon Monoxide over NiO/SnO𝟐 Nanocomposites under UV Irradiation - R. M. Mohamed; Elham S. Aazam (Journal of Nanotechnology)
The NiO/SnO2 nanocomposites have been prepared by the simple coprecipitation method and further characterized by the XRD, SEM, TEM, UV-Vis, and BET. X-ray diffraction (XRD) data analyses indicate the exclusive formation of nanosized particles with rutile-type phase (tetragonal SnO2) for Ni contents below 10 mol%. Only above 10 mol% Ni, the formation of a second NiO-related phase has been determined. The particle size is in the range from 12 to 6 nm. It decreases with increasing amounts of doping NiO. The morphology of NiO-doped SnO2 nanocrystalline powders is spherical, and the distribution of particle size is uniform, as seen from transmission electron microscopy (TEM). The photocatalytic oxidation of CO over NiO/SnO2 photocatalyst has been investigated under UV irradiation. Effects of NiO loading on SnO2, photocatalyst loading, and reaction time on photocatalytic oxidation of CO have been systematically studied. Compared with pure SnO2, the 33.3 mol% NiO/SnO2 composite exhibited approximately twentyfold enhancement of photocatalytic oxidation of CO. Our results provide a method for pollutants removal. Due to simple preparation, high photocatalytic oxidation of CO, and low cost, the NiO/SnO2 photocatalyst will find wide application in the coming future of photocatalytic oxidation of CO.